Renewable Energy Consumption and Economic Growth: a note reassessing panel data results - Pereira, Regina Maria Marques da Fonseca (2020)
We contribute to the renewable energy consumption-income (and growth) nexus literature by performing an empirical study on a worldwide panel data, also accounting for cross-country dependency using a parsimonious specification that accounts for traditional sources of income differences as well as institutional features of the countries. Our results present either negative or nonsignificant influence of the share of renewable energies consumption to economic growth and income.